Investigating the Acceptance of Mobile Library Applications with an Extended Technology Acceptance Model (TAM). (February 2020) - Rafique, Hamaad; Almagrabi, Alaa Omran; Shamim, Azra; Anwar, Fozia; Bashir, Ali Kashif
Abstract: Mobile applications are getting a great deal of interest among researchers due to their proliferation and pervasiveness, especially in the context of digital libraries of educational institutes. However, their low acceptance and usage are observed, hence, in-depth investigations are required in order to understand the factors behind low acceptance and intention to use mobile library application (MLA). Therefore, the aim of this work is to empirically explore the acceptance of MLA with a proposed model that is evolved from the technology acceptance model (TAM). The study objects to deliver empirical provision on acceptance of MLA. A self-administrated cross-sectional survey-based study was conducted to gather data from 340 users of MLA. Structural equation model (SEM) with an analysis of moment structure (AMOS) software was conducted to examine quantitative data. Results revealed that perceived usefulness and perceived ease of use are direct significant predictors with the intention to use MLA whereas system quality and habit are the influencing factors toward the usage intention of MLA. The findings help as a guide for effective decision in the design and development of MLA. Further, the outcomes can be utilized in the resource allocation process for ensuring the success of the library's vision and mission. Highlights: Study on initial acceptance of mobile library application for Pakistani context. Model integrates external factors, habit and system quality in technology acceptance model. Habit and system quality have strong indirect impact on behavioural intention toward mobile library application. Perceived ease of use and perceived usefulness have strong mediating effect on mobile library application usage. Over all, model shows the strong initial acceptance of mobile library application in Pakistan.